2000
DOI: 10.1017/s0007114500000672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity on digestion of nutrients in conventional and germ-free chicks

Abstract: A study was conducted with conventional and germ-free broiler chicks to obtain more information on the role of the intestinal microflora in the anti-nutritive effects of NSP in broiler chicks. As the NSP source, highly methylated citrus pectin (HMC) was used at a dose level of 30 g/kg in a maize-based diet. The diets fed to the germ-free chicks were γ-irradiated, whereas those fed to the conventional chicks were not. Feeding the HMC diet to conventional birds depressed weight gain and food utilization (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 28 publications
(31 reference statements)
2
27
2
Order By: Relevance
“…Under the conditions of this experiment, including the composition of the diet, the basal activities of digestive enzymes did not appear to limit macronutrient digestibility. In any event, the observed digestibilities of starch, protein and fat were rather high when compared with previous work (Smits et al, 1998;Langhout et al, 2000); under such circumstances any improvements in digestibilities would have been impossible, or would have been difficult to detect.…”
Section: Measure Dietcontrasting
confidence: 57%
“…Under the conditions of this experiment, including the composition of the diet, the basal activities of digestive enzymes did not appear to limit macronutrient digestibility. In any event, the observed digestibilities of starch, protein and fat were rather high when compared with previous work (Smits et al, 1998;Langhout et al, 2000); under such circumstances any improvements in digestibilities would have been impossible, or would have been difficult to detect.…”
Section: Measure Dietcontrasting
confidence: 57%
“…This would be consistent with the lack of marked alterations in intestinal architecture and enzyme activities, the lack of increased chloride secretory capacity, and the unaltered growth and ileal digestibility of nutrients in our CMC pigs (present results; Piel et al 2005). Langhout et al (2000), using germ-free chicks, demonstrated that the intestinal microflora contributes to increased digesta viscosity and small-intestinal alterations, and to reduced nutrient digestibility in the small intestine and faeces of birds. Whether bacterial adhesion of pathogenic E. coli to intestinal epithelial cells is influenced by NSP is not known.…”
Section: Carboxymethylcellulose and The Intestinal Microflorasupporting
confidence: 88%
“…Faeces inconsistency might have reflected the water-holding and gelling capacities of CMC, which were maintained in the faeces since CMC is not fermented (Wyatt et al 1988;McDonald et al 2001). Increased water consumption often seen with CMC supplementation (Smits et al 1997;Langhout et al 1999Langhout et al , 2000 might have also contributed to the water retained by CMC in the digesta and to the increased faecal water losses. Improved Na-dependent glucose absorption in the present study is in agreement with the observation that medium-viscosity CMC increased absorption of Na and water in the perfused jejunum of both control rats and those with induced osmotic diarrhoea (Go et al 1994).…”
Section: Carboxymethylcellulose and Intestinal Absorptive And Secretomentioning
confidence: 99%
See 2 more Smart Citations